Rechargeable Lithium-Ion Battery Based on a Cathode of Copper Hexacyanoferrate - Herrera-Diaz, F; Herrera-Diaz, F (IOP Publishing Ltd, 2021)
In this work, the performance of copper(II) hexacyanoferrate(III) (CuHCF) as a cathode material for lithium-ion batteries was studied. The compound was synthesized by a precipitation reaction in aqueous solution in a closed system. The morphology and structure show nanoparticles with sizes between 40 and 70 nm with a high agglomeration and a crystalline phase with a cubic structure, respectively. The material exhibited a stable performance with a working potential of around 3.6 V vs Li+/Li and a decrease in the charge transfer resistance due to increased ionic conductivity. The gravimetric capacity obtained is near 60 mAh g-1 during 300 cycles at a rate of C/20, close to the practical capacity. Considering its electrochemical performance, CuHCF could be a promising cathode material for lithium-ion batteries. © 2021 The Electrochemical Society ("ECS"). Published on behalf of ECS by IOP Publishing Limited.